Pengaruh Waktu Penyimpanan Ekstrak Rennet Abomasum Domba Lokal terhadap Kualitas Keju - Trioso Purnawarman; Chairun Nisa; Karunia Maghfiroh (IPB University, 2012)
The study was aimed to examine the storage effect of rennet extracted from abomasum of local sheep on the texture and organoleptic qualities of cheese including color, flavor, salty taste, and bitter taste. Ten samples of crude rennet extract were divided into two groups which each five samples were stored for 2 weeks and 24 weeks respectively. The rennet extract was then used as milk clotting agent in cheese making process. Streptococcus thermophilus and Lactobacillus bulgaricus were used as starter in those processes. The fresh cheese was coated with beeswax and ripened for 20 days in refrigerator. The ripened cheese was analyzed for the quality. The texture was analyzed by using warner blatzer shear (INSTRON®) and the data were evaluated with completely randomized design (CRD). The result showed that both time storage of rennet extract were not significantly influence on cheese texture (P<0,05). The organoleptic tests of color, flavor, salty taste, and bitter taste were rated by 25 panelists and then the data were analyzed with Friedman test. The time storage of rennet extract resulted variation on organoleptic quality of cheese. Descriptive statistical analyses provided information that each panelist has varied preferences on cheese samples. It can be concluded that the storage of rennet extract had no significantly influence on the texture of cheese and provided variation on organoleptic test. Keywords: storage, rennet extract, cheese, organoleptic test